CLINICAL ANATOMY OF THE LUNGS AND PLEURA (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article provides a thorough examination of the clinical anatomy of the lungs and pleura, highlighting key structures, functions, and their relevance in medical practice. The review incorporates a literature analysis to present current perspectives, a methods section detailing the research approach, results elucidating important findings, and a comprehensive discussion leading to meaningful conclusions and suggestions for future research.